SIFAT FISIKO-KIMIA DAN ORGANOLEPTIK CAKE HASIL SUBSTITUSI TEPUNG TERIGU DENGAN TEPUNG SUWEG - Jenny E. R. Markus; Yuliana Tandi Rubak; Handy Tomasoei (Agriculture Faculty of Flores University, 2012)
This research was conducted in the Seed Technology laboratory and Laboratory of Microbiology, Faculty of Agriculture, University of Nusa Cendana, Kupang, which lasts from September to December 2013 with aims to investigate the influence of substitution of wheat flour with flour suweg the physicochemical properties and organoleptic cake. This study used a completely randomized design (CRD) with 5 treatments, namely substitution suweg flour to wheat flour: 0%, 10%, 20%, 30% and 40%. The parameters analyzed were proximate, softness, porosity, degree of development, test organoleptic colour, flavour, aroma, and texture. Organoleptic data obtained from the 20 panellists and subsequently analyzed by Friedman test, while ANOVA test if there is a real effect then tested further by using DMRT. The results showed that the substitution of different flour suweg provides a very significant effect on water content, fat, ash content, protein, carbohydrate esandtenderness cake. Based on the results of the organoleptic test, cake with flour substitution suweg the colour, aroma and taste of a real significant show, panellists liked the cake substitution suweg 40%, while the texture, the panellists still like to substitution of 40% flour suweg, an assessment of the texture with the highest scores on substitution treatment 10% flour suweg. Organoleptic test and Friedman test results it can be concluded that the cake treatment received a positive response from the panellists was a cake with 40% flour suweg treatment with a total of 66 rankings for colour, aroma as a total ranking of 68, and for a sense of the total ranking of 74. Similarly, some a score on the cake substitution acceptance panellists ranged from 3,1 to 3,4 and the obtained cake was elected with 40% substitution treatment suweg flour.